Study the effect of static magnetic field intensity on drug delivery by magnetic nanoparticles - Abbas Moghanizadeh (Nature Portfolio, 2021)
Abstract Employing the magnets in therapy has a long history of treating diseases, and currently new applications such as drug delivery by magnetic nanoparticles are gaining more attention. This research tried to study the effect of static magnetic field intensity on drug delivery by magnetic nanoparticles carrying thrombolytic agents. In this research, Fe3O4@SiO2 nanoparticles carrying streptokinase were applied. The efficiency of thrombolysis and micro-CT-scan images are utilized to study the effect of different magnetic fields (0.1, 0.2, 0.3 and 0.5 T) on thrombolysis. The results confirm that increasing the static magnetic field intensity accelerated the thrombolysis. Increasing the intensity of the magnetic field from 0.1 to 0.3 T leads to an increase in clot dissolution rate from 55 to 89%, respectively. Moreover, micro-CT-scan images revealed that magnetic nanoparticles carrying a thrombolytic agent penetrated deeper into the mesh-like structure of clot as the magnetic field intensities increased, which could lead to further dissolution of the clot.